Analisis Peran Organisasi Dalam Kegiatan Kelompok Tani “Bajang Peduli” Desa Bungkuk Kecamatan Parang Kabupaten Magetan Untuk Peningkatan Produktivitas - Zidni Ardiana Firdaus; Iza Hanifuddin (Niqosiya: Journal of Economics and Business Research, 2023)
This research is motivated by a form of concern for the problems faced by farmers, especially in the "Bajang Peduli" farmer group in Bungkuk Village, Parang District, Magetan Regency with several problems, namely poverty that still exists among farmers, less than optimal productivity increase, distribution of subsidized fertilizers which is still not optimal for members of farmer groups, the use of infrastructure facilities provided by the government is still lacking due to human resource factors. The primary purpose of this study was to analyze the organization's role in the activities of the "Bajang Peduli" farmer group to increase farmer productivity in Bungkuk Village, Parang District, Magetan Regency. The type of research used is the type of field research. The research was conducted on a farmer group, "Bajang Peduli," in Bungkuk Village, Parang District, Magetan Regency, with data collection techniques using interviews, observation, and documentation. The results of this study indicate that (1) the organization's role in this farmer group's activities still needs to be maximized. (2) The importance of the role of organizations in community activities that have joined the "Bajang Peduli" farmer group is still not fully understood. (3) The impact of the organization's organization's role in the activities of the "Bajang Peduli" farmer group is still not maximally achieved because there are factors that cause and affect farmers' production results. This is evidenced by increasing farmer productivity in Bungkuk Village, Parang District, Magetan Regency.